1999
DOI: 10.1029/1999wr900198
|View full text |Cite
|
Sign up to set email alerts
|

Field observation of flow in a fracture intersecting unsaturated chalk

Abstract: Abstract. Flow through a natural fracture crossing unsaturated chalk in an arid region was investigated in a field experiment using a specially designed experimental setup. The setup allowed complete control of the flow domain inlet and outlet. Water flux into and out of the fracture was measured in small segments of the fracture openings, and flow trajectories were identified using seven fluorobenzoic acid tracers. A 5 day percolation experiment on a 5.3 rn long fracture showed significant spatial and tempora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
58
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(62 citation statements)
references
References 14 publications
4
58
0
Order By: Relevance
“…While fractures in the vadose zone are usually considered as preferential flow paths that serve mainly as water conduits for deep and fast water percolation (Dahan et al, 1999(Dahan et al, , 2000Zhou et al, 2006;Ireson et al, 2009), recent studies have shown that they can serve as air conduits that enhance aeration and water evaporation in deep sections of the vadose zone (Nachshon et al, 2008;Kamai et al, 2009;Weisbrod et al, 2009). It has been shown that, in arid environments, the density gradients between the air within a fracture void (light, wet and warm air) and the atmospheric air (cooler, drier and heavier (denser)) trigger air convection within the void, which enhances water evaporation and salt accumulation in the sediment surrounding the fracture walls (Weisbrod and Dragila, 2006;Kamai et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…While fractures in the vadose zone are usually considered as preferential flow paths that serve mainly as water conduits for deep and fast water percolation (Dahan et al, 1999(Dahan et al, , 2000Zhou et al, 2006;Ireson et al, 2009), recent studies have shown that they can serve as air conduits that enhance aeration and water evaporation in deep sections of the vadose zone (Nachshon et al, 2008;Kamai et al, 2009;Weisbrod et al, 2009). It has been shown that, in arid environments, the density gradients between the air within a fracture void (light, wet and warm air) and the atmospheric air (cooler, drier and heavier (denser)) trigger air convection within the void, which enhances water evaporation and salt accumulation in the sediment surrounding the fracture walls (Weisbrod and Dragila, 2006;Kamai et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Although the basic information that allows adequate characterization of flow and transport in a well-defined medium is relatively well known, the processes occurring in natural heterogeneous environments are still far from being clearly described or properly predicted. Apparently, the difficulty in characterizing water flow and contaminant transport in natural unsaturated zones at the field scale is intimately related to the instability of unsaturated flow [7][8][9][10]. In laboratory experiments where the flow characteristics through a welldefined medium may be controlled, accurate measurements and consequent close calibration of transport models may be achieved.…”
Section: Vadose-zone Monitoring Technologymentioning
confidence: 99%
“…Many observations of irregular and fast -developing wetting patterns, suggest that preferential flow commences before macropores are filled (Nimmo and Mitchell, 2013). However, experimental studies have shown that flow proceeds along localized preferential flow paths (e.g., Dahan et al, 1999;Nicholl et al,1994;Su et al, 1999). For example, an infiltration experiment on a single, in situ, unsaturated fracture in the Negev Chalk, Israel, showed that 70% of water flux was transmitted through less than 20% of the studied fracture openings (Dahan et al, 1999).…”
Section: Conceptual Models Of Infiltration In Unsaturated Chalkmentioning
confidence: 99%
“…However, experimental studies have shown that flow proceeds along localized preferential flow paths (e.g., Dahan et al, 1999;Nicholl et al,1994;Su et al, 1999). For example, an infiltration experiment on a single, in situ, unsaturated fracture in the Negev Chalk, Israel, showed that 70% of water flux was transmitted through less than 20% of the studied fracture openings (Dahan et al, 1999). To account for these inconsistencies, hypotheses related to fluid films on fracture surfaces have been proposed (Tokunaga and Wan, 1997).…”
Section: Conceptual Models Of Infiltration In Unsaturated Chalkmentioning
confidence: 99%